Exploration of the biodiversity and mining novel target genes of Listeria monocytogenes strains isolated from beef through comparative genomics analysis - Zhang, Bo; Sun, Wenjie; Wang, Xiaoxu; Ren, Honglin; Wang, Yang; Hu, Shaohui; Li, Chengwei; Wang, Yuzhu; Hou, Jiaqi; Hu, Xueyu; Shi, Ruoran; Li, Yansong; et al. (Frontiers in Microbiology, 2025)
L. monocytogenes is a significant foodborne pathogen. This study aims to explore the biodiversity and evolutionary characteristics of L. monocytogenes isolated from beef through pan-genome analysis, and to provide important reference value for its specific molecular detection. This study conducted an in-depth analysis of the virulence genes, antimicrobial resistance genes, and environmental resistance genes of 344 L. monocytogenes strains isolated from beef. Pan-genomic analysis revealed that L. monocytogenes from beef have open genomes, providing a solid genetic basis for adaptation to different environments. MLST analysis revealed that the most prevalent types of L. monocytogenes isolated from beef were ST9 and CC9. A total of 50 virulence genes were detected in these strains, with 26 virulence genes such as inlA, inlB, plcA, plcB, and prfA, present in all L. monocytogenes strains. The four most prevalent antibiotic resistance genes in L. monocytogenes were norB, lin, mprF, and FosX, indicating high resistance to fluoroquinolones, lincosamides, peptides, and phosphonic acid antibiotics. A total of 416 potential target genes were identified through pan-genomic screening, which were then further filtered using a hub gene selection method to mining novel target genes. Ultimately, 10 highly connected hub genes were selected: bglF_2, tilS, group_2105, group_2431, oleD, ndk, flgG, purB, pbpB, and fni. These genes play a crucial role in the pathogenesis of L. monocytogenes. The PCR results demonstrated the excellent specificity of the bglF_2 gene for L. monocytogenes. Moreover, in the artificial contamination experiment, the bglF_2 gene was able to effectively detect L. monocytogenes in beef samples. Therefore, the bglF_2 gene holds potential as a specific molecular target for the detection of L. monocytogenes strains in beef samples.